Methodological Aspects of Using Game Technologies in English Language Classes - Inoyatova, Umida Bokhadir qizi (The Lingua Spectrum, 2026)
This article examines the theoretical and practical foundations of using game-based technologies in the education system, particularly in foreign language teaching. It highlights the pedagogical and psychological nature of game activities, their role in students’ personal development, and their linguistic-didactic significance. Game technologies are classified according to didactic objectives, communicative orientation, and modern digital capabilities. Based on the views of leading educational methodologists, the motivational, communicative-cognitive, socio-cultural, therapeutic, and diagnostic functions of games are analyzed and justified. The article presents a methodological model for organizing didactic games for philology students and provides practical recommendations using various interactive games. Additionally, a comparative analysis of modern digital platforms – Baamboozle, Wordwall, JeopardyLabs, and ZEP Quiz – is included. Research findings demonstrate that game technologies effectively enhance student motivation, reinforce grammatical and lexical knowledge, and develop listening, speaking, reading, and writing skills. The study emphasizes the importance of implementing didactic games in a structured, step-by-step manner: brief games at the introductory stage to increase motivation, thematic games in the main stage to consolidate learning, and quizzes or tests in the concluding stage to assess and evaluate students’ knowledge comprehensively.